Lactobacillus rhamnosus CNCM I-3690 decreases subjective academic stress in healthy adults: a randomized placebo-controlled trial. (31st December 2022) - Wauters, Lucas; Van Oudenhove, Luka; Accarie, Alison; Geboers, Karlien; Geysen, Hannelore; Toth, Joran; Luypaerts, Anja; Verbeke, Kristin; Smokvina, Tamara; Raes, Jeroen; Tack, Jan; Vanuytsel, Tim
ABSTRACT: Psychological stress negatively affects the intestinal barrier function in animals and humans. We aimed to study the effect of Lactobacillus rhamnosus CNCM I-3690 on intestinal permeability and stress-markers during public speech. Healthy students were randomized to L. rhamnosus -containing (test) or acidified (placebo) milk consumed twice daily for 4 weeks, with 46 subjects per treatment group. Small intestinal permeability was quantified by a 2 h urinary lactulose–mannitol ratio (LMR, primary outcome), fractional excretion of lactulose (FEL) and mannitol (FEM). Salivary cortisol, State-Trait Anxiety Inventory (STAI) and Perceived Stress scores (PSS) were collected. No between-treatment differences were found for LMR (p = .71), FEL or FEM. Within-treatment analyses showed similar LMR and FEL but a stress-induced increase of FEM with the placebo (p < .05) but not test product. Despite a similar increase in salivary cortisol, the stress-induced increase in STAI was significantly lower with the test product vs. placebo (p = .01). Moreover, a stress-preventative effect of the probiotic was found for PSS and more pronounced in subjects with high stress-induced cortisol (p = .01). While increased FEM was mediated by salivary cortisol levels, the effect of the test product on subjective stress was not mediated by changes in FEM. No serious adverse events occurred. In conclusion, we demonstrated that L. rhamnosus CNCM I-3690 prevented stress-induced hyperpermeability to mannitol. Subjective but not objective stress-markers were reduced with L. rhamnosus vs. placebo, suggesting anxiolytic effects, which were independent of barrier stabilization and attractive for the reduction of stress in both health and disease. Clinicaltrials.gov, number NCT03408691.